Tree age affects carbon sequestration potential via altering soil bacterial community composition and function - Ma, Fengfeng; Liu, Yang; Qi, Youxiang; Deng, Nan; Xiang, Huahao; Qi, Chuanlei; Peng, Pai; Jia, Liming; Zhang, Xuan (Frontiers in Microbiology, 2024)
Among various factors related to forest carbon pool, the tree stand age which interacts with soil organic matter, decomposition rates, and microbial activity, cannot be neglected. However, knowledge about how tree phases influencing soil carbon sinks are not adequate. This study sampled Larix kaempferi (Japanese larch) plantations with different tree stand ages to investigate the temporal dynamics of the forest soil carbon sink. Physiochemical analyses and high throughput sequencing results further revealed the interactions of tree stands and their related rhizosphere microbiome. It was found that microbial composition and metabolic activity were significantly affected by different tree ages, whose structures gradually diversified and became more stable from young to mature forests. Many keystone taxa from phylum Chloroflexi, Proteobacteria, Acidobacteriota, and Nitrospirota were found associated with carbon transformation processes. Interestingly, the carbon resource utilization strategies of microbial groups related to tree ages also differed, with near-mature forest soils performing better labile carbon degradation capacity, and mature forests possessing higher degradation potential of recalcitrant carbon. Age altered tree growth and physiology were found to interact with its rhizosphere microbiome, being the driven factors on the formation and stability of forest soil carbon. This study highlighted the tree age associated soil microbiomes which provided insights into their effects on soil carbon transformation, were significant to enhance the knowledge on carbon sequestration in L. kaempferi plantations.